2017
DOI: 10.1038/nplants.2017.43
|View full text |Cite
|
Sign up to set email alerts
|

GW5 acts in the brassinosteroid signalling pathway to regulate grain width and weight in rice

Abstract: Grain size is a major determinant of grain yield in cereal crops. qSW5/GW5, which exerts the greatest effect on rice grain width and weight, was fine-mapped to a 2,263-bp/21-kb genomic region containing a 1,212-bp deletion, respectively. Here, we show that a gene encoding a calmodulin binding protein, located ∼5 kb downstream of the 1,212-bp deletion, corresponds to qSW5/GW5. GW5 is expressed in various rice organs, with highest expression level detected in young panicles. We provide evidence that the 1,212-bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
317
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 444 publications
(331 citation statements)
references
References 28 publications
12
317
1
1
Order By: Relevance
“…GW5L was co‐expressed with the plasma membrane‐targeted marker, OsSCAMP‐mCherry (Lam et al ) (Figure C). These assays indicated that GW5L was also localized at the plasma membrane, like GW5 (Liu et al ).…”
Section: Resultsmentioning
confidence: 97%
“…GW5L was co‐expressed with the plasma membrane‐targeted marker, OsSCAMP‐mCherry (Lam et al ) (Figure C). These assays indicated that GW5L was also localized at the plasma membrane, like GW5 (Liu et al ).…”
Section: Resultsmentioning
confidence: 97%
“…In Arabidopsis , a kinase cascade consisting of HAIKU1, HAIKU2 , and MINISEED3 promotes seed development zygotically (Luo et al, 2005; Wang et al, 2010), while TTG2 (Garcia et al, 2005), AP2 (Ohto et al, 2009), and ARF2 (Okushima et al, 2005) are engaged in the maternal control of seed size. In rice, QTLs including GS3 (Mao et al, 2010), GS5 (Li et al, 2011), GW2 (Song et al, 2007), GW5 (Liu et al, 2017), GW8 (Wang S. et al, 2012), and GL7 (Wang Y. et al, 2015) were reported to regulate seed size by controlling cell division, while the influence of SRS3 (Kitagawa et al, 2010), D61 (Morinaka et al, 2006), and SRS5 (Segami et al, 2012) on seed size is related to the regulation of cell size. Additionally, the role of GIF1 in carbon partitioning during early seed-filling, which can impact seed weight, has been identified using functional analysis in rice (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In rice, the dephosphorylation of GSK3/SHAGGY-like Kinase (OsGSK2, a rice homolog of Arabidopsis BIN2) releases its suppression on BRASSINAZOLE-RESISTANT1 (OsBZR1), LEAF AND TILLER ANGLE INCREASED CONTROLLER (OsLIC), DWARF AND LOW-TILLERING (OsDLT), OVATE Family Protein 8, and REDUCED LEAF ANGLE1 to activate BR response and increase leaf angle (Bai et al, 2007;Wang, L et al, 2008;Tong et al, , 2012Zhang et al, 2012;Yang et al, 2016, Qiao et al, 2017. The kinase activity of OsGSK2 can also be directly inhibited by membrane protein GW5 (quantitative trait locus for grain width and weight on chromosome 5), which is a calmodulin-binding protein (Liu et al, 2017).…”
mentioning
confidence: 99%